Decreased γ‐aminobutyric acid levels in the brainstem in patients with possible sleep bruxism: A pilot study. (11th October 2017) - Fan, X.; Qu, F.; Wang, J.‐J.; Du, X.; Liu, W.‐C.
Summary: Background: An increasing number of studies have indicated that the central and autonomic nervous systems play roles in the genesis of sleep bruxism (SB). The role of specific neurochemicals in SB has been a subject of interest. Objective: In this study, we use proton magnetic resonance spectroscopy ( 1 H‐MRS) to determine whether the levels of γ‐aminobutyric acid (GABA) and glutamate (Glu) are different in the brainstem and bilateral cortical masticatory area (CMA) between possible sleep bruxism (SB) patients and controls, and discuss whether the brainstem or cortical networks which may affect the central masticatory pathways are under the genesis of SB. Methods: Twelve possible SB patients and twelve age‐ and gender‐matched controls underwent 1 H‐MRS using the "MEGA‐Point Resolved Spectroscopy Sequence" (MEGA‐PRESS) technique in the brainstem and bilateral CMA. Proton magnetic resonance spectroscopy data were processed using LCModel. Because the signal detected by MEGA‐PRESS includes contributions from GABA, macromolecules (primarily proteins) and homocarnosine, the GABA signal is referred to as "GABA+". The glutamate complex (Glx) signal contains both glutamate (Glu) and glutamine (Gln), which mainly reflect glutamatergic metabolism. Results: Edited spectra were successfully obtained from the bilateral CMA in all subjects. There were no significant differences in neurochemical levels between the left and right CMA in possible SB patients and controls. In the brainstem, significantly lower GABA+ levels were found in possible SB patients than in controls ( P = .011), whereas there was no significant difference ( P = .307) in Glx levels between the 2 groups. Conclusions: SB patients may possess abnormalities in the GABAergic system of brainstem networks.